PEMBELAJARAN INKUIRI UNTUK MELATIH LITERASI SAINS SISWA PENDIDIKAN DASAR - Puspa Wulan Aprilia; Suryanti Suryanti; Nadi Suprapto (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Learning strategies must be well defined and built to train students' scientific literacy. Scientific literacy is very important for a person because the progress of a nation is determined by the quality of human resources who are literate in science and technology. One of the lessons that can be applied in training literacy is inquiry learning. However, the technique of inquiry learning in training students' scientific literacy still needs to be studied. This article aims to conduct an in-depth study of inquiry learning to train elementary school students' scientific literacy. The conclusion is that the scientific literacy of elementary school students must be trained. Learning that can be used to train scientific literacy is through inquiry learning. In inquiry learning must pay attention to the characteristics, characteristics, principles, stages of implementation, and advantages and disadvantages. In training scientific literacy, you must pay attention to competencies, indicators, and learning steps.